MORALNO-ETICHNA PROBLEMATICA OF SMALL PROSE OF NICK YANOVSKY - PLETSEN, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article analyzes the prose of Mykola Yanovskiy; reveals the problematics, ideological and imaginative world of his short stories and stories. The author discovers the features of artistic thinking of the writer.